Vertical nanocrystalline / amorphous tungsten trioxide electrochromic film and preparation method and application thereof

By preparing zinc oxide nanorod templates on conductive substrates and preparing vertical nanocrystalline/amorphous tungsten trioxide electrochromic films by electrochemical deposition methods, the existing tungsten trioxide films in terms of cycle stability and optical modulation capabilities are solved. Inadequately, efficient electrochemical reactions and excellent optical properties are achieved.

CN119430684APending Publication Date: 2025-02-14HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411684401.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing tungsten trioxide electrochromic films have shortcomings in cyclic stability and optical modulation capabilities, especially in terms of discoloration velocity and near-infrared band modulation capabilities.

Method used

By using zinc oxide nanorods as induction templates, vertical nanocrystalline/amorphous tungsten trioxide electrochromic films were prepared by electrochemical deposition method, and the preparation of a vertical structure nanocrystalline tungsten trioxide porous nanosheet film was achieved.

Benefits of technology

The film has high cyclic stability and electrochemical activity, and exhibits independent and large optical modulation capabilities, faster color discoloration speed and excellent cyclic stability in the visible/near infrared band.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430684A_ABST
    Figure CN119430684A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochromic films, and particularly relates to a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film and a preparation method and application thereof. The preparation method of the film comprises the following steps: S1, vertically placing a cleaned conductive substrate in a reaction kettle, and adding a zinc oxide precursor solution into the reaction kettle for hydrothermal reaction to obtain a zinc oxide nanorod film template; and S2, placing the zinc oxide nanorod film template obtained in the step S1 as a working electrode in an electrolyte for electrodeposition of tungsten trioxide, taking silver / silver chloride as a reference electrode, taking a platinum sheet as a counter electrode, performing electrochemical deposition of tungsten trioxide, and performing cleaning and drying to obtain the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film. The thin film has independent and relatively high optical modulation capability in a visible light / near-infrared band, relatively high color changing speed and relatively good cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochromic films, and in particular relates to a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film and a preparation method and application thereof. Background Art

[0002] Electrochromism refers to the phenomenon that the optical properties of a device (such as transmittance and reflectivity) undergo reversible and lasting changes under the stimulation of a small external voltage. Electrochromic devices have broad application prospects in optoelectronic devices such as smart windows, anti-counterfeiting labels, and anti-glare rearview mirrors. As a typical electrochromic material, tungsten trioxide has pure color and high chemical stability, and has therefore been widely and deeply studied.

[0003] At present, common tungsten trioxide materials usually face various problems. For example, the crystalline tungsten trioxide film synthesized by magnetron sputtering, hydrothermal method or high-temperature heat treatment has good cycle stability, but the film is usually dense and has fewer internal ion transmission paths, so the color change speed is usually slow and the near-infrared band modulation ability is poor; the tungsten trioxide film synthesized by electrochemical deposition is usually an amorphous dense film. Although it has a relatively large optical modulation ability, it is difficult to maintain the original structure during the long-term electrochemical cycle and cannot meet the needs of practical applications. Therefore, it is crucial to accurately design the crystal structure and micromorphology of the material and prepare a tungsten trioxide electrochromic film with both high cycle stability and large and independent visible light and near-infrared modulation capabilities to promote its practical application.

[0004] The vertically arranged nanocrystalline structure can provide a direct ion and electron transmission path, increase the specific surface area of ​​the material, provide more active sites for electrochemical reactions, thereby improving the electrochemical activity of the material, significantly improving the transmission efficiency and reversibility of ions and electrons in the film, thereby achieving faster reaction kinetics and better cycle stability. However, it is difficult to prepare nanocrystalline materials with a vertical structure, and there are few reports on vertical tungsten trioxide nanocrystals / amorphous materials. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, which uses a zinc oxide nanorod as an induction template to achieve the preparation of a vertical structured nanocrystalline tungsten trioxide porous nanosheet film. The preparation method is simple, the reaction conditions are relatively mild, high temperature heat treatment and subsequent template removal are not required, it is energy-saving and environmentally friendly, and it is convenient for large-scale preparation.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film comprises the following steps:

[0008] S1: Template preparation

[0009] The cleaned conductive substrate is placed vertically in a reaction kettle, and a zinc oxide precursor solution is added into the reaction kettle for hydrothermal reaction to obtain a zinc oxide nanorod film template;

[0010] S2: Deposition of tungsten trioxide film

[0011] The zinc oxide nanorod film template obtained in step S1 is placed in the electrolyte of electrodeposited tungsten trioxide as a working electrode, silver / silver chloride is used as a reference electrode, and a platinum sheet is used as a counter electrode. Tungsten trioxide is electrochemically deposited, and after cleaning and drying, a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film is obtained.

[0012] Furthermore, the temperature of the hydrothermal reaction in step S1 is 80-100° C., and the time of the hydrothermal reaction is 3-5 hours.

[0013] Furthermore, the preparation of the zinc oxide precursor solution in step S1 is specifically as follows: zinc acetate and hexamethylenetetramine are dissolved in water; the molar ratio of zinc acetate to hexamethylenetetramine is 1:(0.5-1.5).

[0014] Furthermore, the conductive substrate in step S1 is selected from one of fluorine-doped tin oxide conductive glass, indium tin oxide conductive glass, and indium tin oxide polyethylene terephthalate plastic flexible conductive substrate.

[0015] Furthermore, the preparation method of the electrolyte for electrodeposition of tungsten trioxide in step S2 is: adding hydrogen peroxide to an aqueous solution of sodium tungstate, then adding a perchloric acid solution to adjust the pH to 1-2, and stirring to obtain the electrolyte.

[0016] Furthermore, the concentration of the sodium tungstate aqueous solution is 10-20 mmol / L, the molar ratio of the sodium tungstate to hydrogen peroxide is 1:(2-3); and the concentration of the perchloric acid solution is 70-72 wt%.

[0017] Furthermore, in step S2, the deposition potential of the electrochemical deposition is -0.5 to -0.9 V vs. Ag / AgCl, and the deposition time is 400 to 1000 s.

[0018] The second purpose of the present invention is to provide a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, whose vertical nanocrystalline structure and porous nanosheet morphology provide sufficient ion / electron transmission paths for electrochemical reactions, and the film has both the high electrochemical activity of amorphous tungsten trioxide and the good cycle stability of crystalline tungsten trioxide. It has independent and large optical modulation ability, fast color change speed and good cycle stability in the visible light / near infrared band.

[0019] To achieve the above object, the present invention adopts the following technical solutions:

[0020] A vertical nanocrystalline / amorphous tungsten trioxide electrochromic film is prepared by using the above preparation method.

[0021] The third object of the present invention is to provide an application of a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, which has industrial and promotion value.

[0022] To achieve the above object, the present invention adopts the following technical solutions:

[0023] The application of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film is used in the preparation of electrochromic materials.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention uses zinc oxide nanorods as an induction template, which acts as a conductor in the electrochemical reaction and can also generate a micro-area electric field near the nanorods, thereby inducing the tungsten trioxide precursor ions (W2O 11 2- ) are oriented along the zinc oxide nanorods, realizing the preparation of vertically structured nanocrystalline / amorphous tungsten trioxide electrochromic films.

[0026] (2) The vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared by the present invention has a nanocrystalline structure vertically embedded in an amorphous matrix and a porous nanosheet microstructure. Compared with the traditional tungsten trioxide film, the constructed vertically arranged nanocrystalline / amorphous dual-phase structure can simultaneously improve the cycle stability and electrochemical activity of the tungsten trioxide film; the vertical arrangement of nanocrystals provides a more efficient ion / electron transmission channel, promotes the effective transport of electrons and ions in the film, and improves the ion / electron deintercalation efficiency and reversibility; the porous nanosheet morphology can effectively increase the contact area between the film and the electrolyte, and increase the number of exposed reaction active sites in the film, thereby synergistically improving the optical modulation range, reaction kinetics and cycle stability of the film.

[0027] (3) The vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared by the present invention exhibits a response time of less than 3s at 1000nm, an optical modulation range of more than 98.0% and a cycle stability of more than 3000 cycles. The nanocrystalline / amorphous tungsten trioxide electrochromic film with a vertical arrangement structure can still maintain 95% of the initial optical modulation range after 3000 electrochemical cycles. Therefore, it can be well applied to the fields of electrochromic materials and has industrialization and promotion value.

[0028] (4) The preparation method provided by the present invention is simple, the reaction conditions are relatively mild, no high-temperature heat treatment and subsequent removal of the template are required, it is energy-saving and environmentally friendly, and it is convenient for large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a schematic diagram of the preparation principle of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film of the present invention;

[0030] Figure 2 is a current-time curve diagram of the electrodeposition process of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic thin film prepared in Example 1;

[0031] Figure 3 Schematic diagram of the formation process of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1;

[0032] Figure 4 Surface scanning electron microscope (SEM) images of films with different deposition times: Figure 4 a is the SEM image of the zinc oxide film surface before deposition begins; Figure 4 b is the SEM image of the film surface after deposition for 10 s; Figure 4 c is the SEM image of the film surface after 50 s of deposition; Figure 4 d is the SEM image of the film surface at 200 s of deposition; Figure 4 e is the SEM image of the film surface at 600 s of deposition; Figure 4 f is the SEM image of the film cross section at 600s of deposition;

[0033] Figure 5 It is the Raman spectra of vertical nanocrystalline / amorphous tungsten trioxide electrochromic films at different deposition time periods;

[0034] Figure 6 is the XRD pattern of the film; Figure 6 a is the XRD pattern of the zinc oxide nanorod film prepared in Example 1; Figure 6 b is the XRD spectrum of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1;

[0035] Figure 7 is a TEM spectrum of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1;

[0036] Figure 8 is the XPS spectrum of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1; Figure 8 a is the full spectrum, Figure 8 b is the fine spectrum of tungsten element;

[0037] Fig. 9The vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 is 20mV·s -1 Cyclic voltammetry curves below;

[0038] Fig.10 is a transmittance curve of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 at different voltages;

[0039] Fig.11 is a graph showing the variation of the in-situ transmission spectrum and optical density of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 with the charge density; Fig.11 a, 11b are the in-situ transmission spectra and optical density curves of the film at 1000nm with a square wave voltage of -0.7V and 1.0V (relative to the silver wire) at an interval of 30s as a function of charge density; Fig.11 c and 11d are the curves of the in-situ transmission spectrum and optical density of the film at 633 nm as a function of charge density;

[0040] Fig.12 This is a test curve of the optical cycle stability of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 at 1000nm under the application of a square wave voltage of -0.7V and 1.0V (relative to the silver wire) with an interval of 30s. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further explained below in conjunction with specific embodiments, test examples and drawings.

[0042] In the following examples and test examples, the raw materials and preparation methods used are conventional materials and techniques in the art unless otherwise specified.

[0043] like Figure 1 As shown in the figure, the construction strategy of the vertical nanocrystalline / amorphous dual-phase tungsten trioxide film of the present invention is as follows: the present invention prepares a zinc oxide nanorod array perpendicular to the substrate on a conductive substrate, which is used to construct a directional electric field in the subsequent electrodeposition process; then, a micro-region directional electric field perpendicular to the conductive substrate is generated by the zinc oxide nanorods, and the tungsten trioxide nanocrystals in the electrodeposition solution are vertically arranged around the directional electric field. At the same time, the zinc oxide nanorods are in-situ etched by an acidic electrolyte, thereby successfully preparing a nanocrystalline / amorphous tungsten trioxide electrochromic film with a vertical structure.

[0044] Example 1

[0045] Example 1 provides a method for preparing a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, and the preparation steps are as follows:

[0046] S1: Template preparation

[0047] The zinc oxide precursor solution is prepared by dissolving zinc acetate and hexamethylenetetramine in deionized water at a molar ratio of 1:1 to obtain zinc acetate precursor solution at a concentration of 20 mmol / L.

[0048] The fluorine-doped tin oxide conductive glass (FTO) substrate was immersed in acetone, deionized water, and ethanol, respectively, and ultrasonically cleaned for 15 minutes, and then dried with nitrogen to obtain a cleaned conductive substrate. The cleaned conductive substrate was placed vertically in a reactor, and a zinc oxide precursor solution was added to the reactor. The reaction was carried out at 90°C for 3 hours for hydrothermal reaction. After the reaction was completed, the substrate was cooled to room temperature, the conductive substrate was taken out, and it was fully rinsed and dried to obtain a zinc oxide nanorod film template.

[0049] S2: Deposition of tungsten trioxide film

[0050] According to the molar ratio of sodium tungstate dihydrate to hydrogen peroxide of 1:2.5, 30wt% hydrogen peroxide was added to a 13mmol / L sodium tungstate dihydrate aqueous solution, and the pH of the mixed solution was adjusted to 1.2 using a 72wt% perchloric acid solution. The mixture was stirred at room temperature for 24h to obtain an electrolyte for electrodeposition of tungsten trioxide.

[0051] The zinc oxide nanorod film template obtained in step S1 is placed as a working electrode in the electrolyte of tungsten trioxide electrodeposition, silver / silver chloride is used as a reference electrode, and a platinum sheet is used as a counter electrode. The constant voltage mode of the electrochemical workstation is used, and the deposition potential is set to -0.7Vvs.Ag / AgCl. The deposition time is 600s for electrochemical deposition. After cleaning and drying, an electrochromic film with vertical nanocrystals / amorphous tungsten trioxide is obtained.

[0052] Example 1 also provides a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, which is prepared by the above preparation method.

[0053] Example 2

[0054] Example 2 provides a method for preparing a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, and the preparation steps are as follows:

[0055] S1: Template preparation

[0056] The zinc oxide precursor solution is prepared by dissolving zinc acetate and hexamethylenetetramine in deionized water at a molar ratio of zinc acetate to hexamethylenetetramine of 1:0.5, so that the concentration of zinc acetate is 25 mmol / L.

[0057] The indium tin oxide conductive glass (ITO) substrate was immersed in acetone, deionized water, and ethanol, respectively, and ultrasonically cleaned for 15 minutes, and then dried with nitrogen to obtain a cleaned conductive substrate. The cleaned conductive substrate was placed vertically in a reactor, and a zinc oxide precursor solution was added to the reactor. The reaction was carried out at 80°C for 5 hours for hydrothermal reaction. After the reaction was completed, the substrate was cooled to room temperature, and the conductive substrate was taken out and fully rinsed and dried to obtain a zinc oxide nanorod film template.

[0058] S2: Deposition of tungsten trioxide film

[0059] According to the molar ratio of sodium tungstate dihydrate to hydrogen peroxide of 1:3, 30wt% hydrogen peroxide was added to a 20mmol / L sodium tungstate dihydrate aqueous solution, and the pH of the mixed solution was adjusted to 2 using a 70wt% perchloric acid solution. The mixture was stirred at room temperature for 24h to obtain an electrolyte for electrodeposition of tungsten trioxide.

[0060] The zinc oxide nanorod film template obtained in step S1 is placed as a working electrode in the electrolyte of tungsten trioxide electrodeposition, silver / silver chloride is used as a reference electrode, and a platinum sheet is used as a counter electrode. The constant voltage mode of the electrochemical workstation is used, and the deposition potential is set to -0.9Vvs.Ag / AgCl. The deposition time is 1000s for electrochemical deposition to obtain a tungsten trioxide film. After cleaning and drying, a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film is obtained.

[0061] Example 2 also provides a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, which is prepared using the above preparation method.

[0062] Example 3

[0063] Example 3 provides a method for preparing a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, and the preparation steps are as follows:

[0064] S1: Template preparation

[0065] The zinc oxide precursor solution is prepared by dissolving zinc acetate and hexamethylenetetramine in deionized water at a molar ratio of 1:1.5 so that the concentration of zinc acetate is 20 mmol / L.

[0066] The indium tin oxide polyethylene terephthalate plastic flexible conductive substrate (ITO / PET) substrate was immersed in acetone, deionized water, and ethanol, respectively, and ultrasonically cleaned for 15 minutes, and then dried with nitrogen to obtain a cleaned conductive substrate. The cleaned conductive substrate was placed vertically in a reactor, and a zinc oxide precursor solution was added to the reactor. The reaction was carried out at 100°C for 4 hours for hydrothermal reaction. After the reaction was completed, it was cooled to room temperature, the conductive substrate was taken out, and it was fully rinsed and dried to obtain a zinc oxide nanorod film template.

[0067] S2: Deposition of tungsten trioxide film

[0068] According to the molar ratio of sodium tungstate dihydrate to hydrogen peroxide of 1:2, 30wt% hydrogen peroxide was added to a 10mmol / L sodium tungstate dihydrate aqueous solution, and the pH of the mixed solution was adjusted to 1 using a 70wt% perchloric acid solution. The mixture was stirred at room temperature for 24h to obtain an electrolyte for electrodeposition of tungsten trioxide.

[0069] The zinc oxide nanorod film template obtained in step S1 is placed as a working electrode in the electrolyte of electrodeposited tungsten trioxide, silver / silver chloride is used as a reference electrode, and a platinum sheet is used as a counter electrode. The constant voltage mode of the electrochemical workstation is used, and the deposition potential is set to -0.5Vvs.Ag / AgCl. The deposition time is 400s to perform chemical deposition to obtain a tungsten trioxide film. After cleaning and drying, a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film is obtained.

[0070] Example 3 also provides a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, which is prepared by the above preparation method.

[0071] Test Example 1

[0072] Analysis of the formation process of vertical nanocrystalline / amorphous tungsten trioxide electrochromic films

[0073] (1) Growth process of vertical nanocrystalline / amorphous tungsten trioxide electrochromic films

[0074] The growth process of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film obtained in Example 1 was analyzed by the current-time curve diagram. The results are as follows: Figure 2 shown.

[0075] Figure 2 This is a current-time curve of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film obtained in Example 1. Figure 2 As shown, according to the trend of current density change, it can be divided into three stages, marked as stage I, stage II and stage III. In stage I, the initial current density is large, and then gradually decreases, representing the dissolution of zinc oxide nanorods and the nucleation of tungsten trioxide precursor. In stage II, the current density increases slightly, representing the early growth process of tungsten trioxide. In stage III, the current density gradually decreases and eventually stabilizes, representing the steady growth process of tungsten trioxide. The reaction equation occurring near zinc oxide nanorods is as follows:

[0076] Formula 1: 2WO4 2- +4H2O2→W2O 11 2- +2OH - +3H2O

[0077] Formula 2: ZnO + 2H+ →Zn 2+ +H2O

[0078] Formula 3:

[0079] As shown in equation 1-3, sodium tungstate in the electrolyte reacts with hydrogen peroxide to generate W2O 11 2- ions; zinc oxide reacts with hydrogen ions in the electrolyte, causing the zinc oxide nanorod template to gradually dissolve; W2O in the solution 11 2- Under the combined action of hydronium ions and electrons, ions generate H x WO3·2H2O nanocrystals. At a relatively far distance from the ZnO nanorods, W2O 11 2- The ions eventually form amorphous H x WO3, as shown in Equation 4.

[0080] Formula 4:

[0081] (2) Formation process of vertical nanocrystalline / amorphous tungsten trioxide electrochromic film

[0082] Example 1 Schematic diagram of the formation process of vertical nanocrystalline / amorphous tungsten trioxide electrochromic film Figure 3 As shown. When the zinc oxide nanorod template is immersed in the electrolyte, the electrolyte adheres to the surface of the zinc oxide nanorods and between the rods due to capillary force to form a liquid film; then, with the help of the directional electric field along the direction of the nanorods, the surface of the zinc oxide nanorods and the position wrapped by the liquid film preferentially nucleate and grow to form a vertical nanocrystalline structure; then, tungsten trioxide further grows at the nucleated position, and finally forms a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film.

[0083] (3) Morphological evolution of vertical nanocrystalline / amorphous tungsten trioxide electrochromic films

[0084] The morphological evolution process from ZnO nanorod film to vertical nanocrystalline / amorphous tungsten trioxide electrochromic film was visually observed using SEM. Figure 4 shown.

[0085] Figure 4 The following are surface scanning electron microscope (SEM) images of the films deposited at different times in Example 1: Figure 4 a is the SEM image of the zinc oxide film surface before deposition begins; Figure 4 b is the SEM image of the film surface after deposition for 10 s; Figure 4 c is the SEM image of the film surface after 50 s of deposition; Figure 4d is the SEM image of the film surface at 200 s of deposition; Figure 4 e is the SEM image of the film surface at 600 s of deposition; Figure 4 f is the SEM image of the film cross section at 600s of deposition. Figure 4 As shown in a, before the deposition begins, the surface of the zinc oxide film has a hexagonal nanorod array morphology. Figure 4 As shown in Fig. b, after 10 seconds of deposition (stage I), the film surface basically maintains the nanorod morphology, but the diameter of the nanorod increases significantly, and the cross-section of the nanorod changes from hexagonal to circular or elliptical. Figure 4 As shown in Figure c, after 50 seconds of deposition (stage II), the surface of the nanorods becomes rough, the regular nanorod structure disappears, and the nanoparticles fill the gaps between adjacent nanorods, beginning to form a nanosheet morphology. Figure 4 As shown in Figure d, after 200s of deposition (stage III), the film surface is a nanosheet morphology assembled by nanoparticles. Figure 4 As shown in Figure e, after 600 s of deposition, a porous nanosheet array was formed. Figure 4 As shown in f, the nanocrystalline / amorphous tungsten trioxide electrochromic film with a vertically arranged structure is about 610nm.

[0086] (4) Composition changes during the reaction from ZnO nanorod film to vertical nanocrystalline WO3

[0087] Raman spectra of vertical nanocrystalline / amorphous tungsten trioxide electrochromic films at different deposition time periods are shown in Figure 2. Figure 5 As shown. Figure 5 It can be seen that as the electrochemical deposition reaction proceeds, zinc oxide at 437 cm -1 The characteristic peak at 960 cm -1 The characteristic peak of the terminal W=O bond stretching mode appeared nearby, proving that as the electrochemical reaction proceeded, the zinc oxide nanorods induced the template to gradually dissolve and tungsten trioxide gradually grew.

[0088] Test Example 2

[0089] Composition and structure analysis of vertical nanocrystalline / amorphous tungsten trioxide electrochromic films

[0090] The zinc oxide nanorod film template and the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 were detected by an X-ray diffraction (XRD) analyzer. Figure 6 The vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 was observed using a transmission electron microscope (TEM). Figure 7 The vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 was analyzed by X-ray photoelectron spectroscopy (XPS). Figure 8 shown.

[0091] Figure 6 a is the XRD spectrum of the zinc oxide nanorod film prepared in Example 1. It can be observed that the zinc oxide nanorod film prepared in Example 1 belongs to hexagonal zinc oxide (JCPDS No.36-1451) and has a strong (002) peak, indicating that the zinc oxide nanorod film prepared in Example 1 has orientation in the vertical direction. Figure 6 b is the XRD spectrum of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1. It can be observed that the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 belongs to monoclinic tungsten trioxide dihydrate (JCPDS No.18-1420), in which a strong (001) peak can be observed, indicating that the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 has an orientation of preferential growth along (001).

[0092] Figure 7 This is the TEM spectrum of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1. Figure 7 It can be seen that the film presents a nanocrystalline structure dispersed in an amorphous matrix, and the lattice spacing of the nanocrystalline part is 0.370 nm, corresponding to the (001) crystal plane of tungsten trioxide dihydrate, which is consistent with the XRD results.

[0093] Figure 8 This is the XPS spectrum of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1. Figure 8 a is the full spectrum, Figure 8 b is the fine spectrum of tungsten element. Figure 8 It is known that the spectrum shows the characteristic peaks of W4f, O1s and C1s, but no characteristic peak of zinc, indicating that only W and O elements exist in the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, proving that the zinc oxide template is removed simultaneously during the electrochemical deposition of tungsten oxide. Figure 8 b shows that W in its highest oxidation state, W 6+ Form exists.

[0094] Test Example 3

[0095] Characterization of properties of vertical nanocrystalline / amorphous tungsten trioxide electrochromic films

[0096] The electrochemical workstation and UV-visible spectrophotometer were used to test the electrochemical and electrochromic properties of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, as follows:

[0097] I. A three-electrode test system was assembled with 0.1 mol / L sulfuric acid aqueous solution as the electrolyte, vertical nanocrystalline / amorphous tungsten trioxide electrochromic film as the working electrode, and silver wire and platinum wire as the reference electrode and counter electrode respectively. Test 20 mV·s -1 Below, the cyclic voltammetry curve of vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, see Fig. 9 shown.

[0098] II. Apply voltages of -0.7V, -0.2V and 0.2V (relative to the silver wire) to the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, and measure the transmittance change value of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film in the wavelength range of 300 to 1300nm, see Fig.10 shown.

[0099] III. The in-situ transmission spectra and the relationship between the optical density and the charge density of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film at 1000nm and 633nm under the application of -0.7V and 1.0V (relative to the silver wire) square wave voltage with an interval of 30s were tested, see Fig.11 shown.

[0100] IV. The optical cycling stability of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film at 1000nm was tested under the application of a square wave voltage of -0.7V and 1.0V (relative to the silver wire) with an interval of 30s, see Fig.12 shown.

[0101] Fig. 9 The vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 is 20mV·s -1 Cyclic voltammetry curves. Fig. 9 It is known that the process includes the injection / extraction of hydrogen ions and electrons, the larger peak current density and the area enclosed by the curve confirm that the prepared vertical nanocrystalline / amorphous tungsten trioxide electrochromic film has high electrochemical activity.

[0102] Fig.10 The vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 has a transmittance curve at different voltages. Fig.10 It can be seen that after applying voltages of -0.7V and 0.2V, the optical modulation ranges of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 are 98.3% and 98.0% at 633nm and 1000nm, respectively.

[0103] Fig.11 is a graph showing the variation of the in-situ transmission spectrum and optical density of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 with the charge density; Fig.11a, 11b are the in-situ transmission spectra and optical density curves of the film at 1000nm with a square wave voltage of -0.7V and 1.0V (relative to the silver wire) at an interval of 30s as a function of charge density; Fig.11 c and 11d are the in-situ transmission spectra of the film at 633nm and the curves of the optical density changing with the charge density. Fig.11 It is known that the coloring efficiency of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 at 1000nm and 633nm is 220.7cm 2 C -1 and 99.2cm 2 C -1 , the coloring time at 1000nm is 2.5s, the fading time is 2.6s, the coloring time at 633nm is 6.4s, and the fading time is 7.2s.

[0104] Fig.12 This is a graph of the optical cycle stability test of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 at 1000nm under the application of a square wave voltage of -0.7V and 1.0V (relative to the silver wire) with an interval of 30s. Fig.12 It is known that after 3000 electrochemical cycles, 95% of the initial optical modulation range can still be maintained. It can be seen that the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film prepared in Example 1 has the advantages of a large optical simulation adjustment range in the visible and infrared bands and good cycle performance.

[0105] The above are only preferred embodiments of the present invention, and are not limited to the above examples. For those skilled in the art, various changes and variations are possible under the principle of the present invention. Any modifications and improvements made should be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, characterized in that: The following steps are involved: S1: Template preparation The cleaned conductive substrate is placed vertically in a reaction kettle, and a zinc oxide precursor solution is added into the reaction kettle for hydrothermal reaction to obtain a zinc oxide nanorod film template; S2: Deposition of tungsten trioxide film The zinc oxide nanorod film template obtained in step S1 is placed in the electrolyte of electrodeposited tungsten trioxide as a working electrode, silver / silver chloride is used as a reference electrode, and a platinum sheet is used as a counter electrode. Tungsten trioxide is electrochemically deposited, and after cleaning and drying, a vertical nanocrystalline / amorphous tungsten trioxide electrochromic film is obtained.

2. The method for preparing the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step S1 is 80-100° C., and the time of the hydrothermal reaction is 3-5 hours.

3. The method for preparing the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film according to claim 1, characterized in that: The zinc oxide precursor solution in step S1 is prepared specifically by dissolving zinc acetate and hexamethylenetetramine in water; the molar ratio of zinc acetate to hexamethylenetetramine is 1:(0.5-1.5).

4. The method for preparing the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film according to claim 1, characterized in that: The conductive substrate in step S1 is selected from one of fluorine-doped tin oxide conductive glass, indium tin oxide conductive glass, and indium tin oxide polyethylene terephthalate plastic flexible conductive substrate.

5. The method for preparing the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film according to claim 1, characterized in that: The preparation method of the electrolyte for electrodeposition of tungsten trioxide in step S2 is: adding hydrogen peroxide to an aqueous solution of sodium tungstate, then adding a perchloric acid solution to adjust the pH to 1-2, and stirring to obtain the electrolyte.

6. The method for preparing the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film according to claim 5, characterized in that: The concentration of the sodium tungstate aqueous solution is 10-20 mmol / L, the molar ratio of the sodium tungstate to hydrogen peroxide is 1:(2-3); the concentration of the perchloric acid solution is 70-72 wt%.

7. The method for preparing the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film according to claim 1, characterized in that: The deposition potential of the electrochemical deposition in step S2 is -0.5 to -0.9 V vs. Ag / AgCl, and the deposition time is 400 to 1000 s.

8. A vertical nanocrystalline / amorphous tungsten trioxide electrochromic film, characterized in that: The preparation method according to claim 1 is used for preparation.

9. The use of the vertical nanocrystalline / amorphous tungsten trioxide electrochromic film as claimed in claim 8, characterized in that: Application in the preparation of electrochromic materials.